CONTEMPORARY CURATING, ARTISTIC REFERENCE AND PUBLIC RECEPTION reconsidering inclusion,... transparency and mediation in exhibition making pr. - Bertrand, Stéphanie. ([S.l.] : ROUTLEDGE, 2021)
Contemporary Curating, Artistic Reference and Public Reception undertakes a unique critical survey and analysis of prevailing group exhibition-making practices in Europe, the UK and North America. Drawing on curatorial literature and two in-depth case studies of group exhibitions, Bertrand advocates for a mode of curatorial practice that secures the content of artworks, in contrast to prevailing open-ended, indeterminate approaches. Proposing a third exhibition type beyond the current binary exhibition ontology that opposes art historical narratives to curatorial installations or Gesamtkunstwerk, the book directly tackles the enduring critique of curating as a mediating activity that produces sameness in group-exhibition contexts by establishing artistic equivalences. The book relies on the principles of analytical philosophy to assess how different exhibition-making approaches fix reference and determine artistic reception, reintroducing a standard to evaluate exhibitions beyond personal taste and thematic coherence. Bertrand ultimately proposes an alternative conception of practice that affirms the renewed relevance of the institutional group show in the present context. Contemporary Curating, Artistic Reference and Public Reception will be of interest to academics, researchers and students working in museum and curatorial studies, visual cultures, art theory and art history programmes. Art theorists and critics, as well as curators of contemporary art with a research-based practice, should also find much to interest them within the pages of the book.
OCLC-licensed vendor bibliographic record.
Keywords: Art museums -- Curatorship; Art -- Exhibitions; ART / General; ART / Criticism